Parasitism of Spalangia cameroni (Hymenoptera, Pteromalidae), an idiobiont parasitoid on pupae of Ceratitis capitata (Diptera, Tephritidae) - Pérez-Hinarejos, Marta; Beitia, Francisco J. (IOBC/wprs, 2021)
Spalangia cameroni Perkins, 1910 is a pteromalid hymenopteran, well known as a pupal parasitoid of flies belonging to different taxonomic families in the order Diptera, as Muscidae, Sarcophagidae and Anthomyiidae. This species is being used as a biological control agent against the housefly (Musca domestica) and the stable fly (Stomoxys calcitrans). In the family Tephritidae it was known as a parasitoid of Anastrepha suspensa, Dacus cucurbitae and D. passiflorae, but recently it has been described as a parasitoid of the Mediterranean Fruit Fly, Ceratitis capitata, in the Valencian Community (Spain). Due to the importance of that fruit fly species as a serious pest on citrus and fruit trees, it has been started the rearing and the biological study of S. cameroni in laboratory conditions, in order to know its ability to be used in the biological control of the medfly. Biological and parasitic parameters of the insect, as adult longevity, female fecundity and fertility, influence of host age and temperature on parasitism and female ability in searching the host buried in the ground, are being analysed.